The Larval Trematode Infecting Fresh Water Snails in the Girana Dam and Surrounding Water Resources at Nandgaon Tehsil of Nashik District, (M.S.) India - Ghatule2, Dada M. Kadam3 and Nilkanth V.Suryawanshi4, Laxman S. Chandore1*, Varsharani A. (Journal of Ecobiotechnology, 2011)
The present research focuses on the different larval trematodes infecting intermediate host i.e. snails in the Girana dam and surrounding water resources in Nanadgaon tehsil of Nashik district. Author collected snails from ponds, streams and river etc. of the selected site where livestock like, cows, Buffalos, Goats and sheep’s visit continuously for drinking water .These snails were dissected in laboratory to study host parasite system. The common larvae found responsible for the infection of Snails are Cercarie, Metacercarie, Redia etc. The different species of infected snails like Melania scabra, Lymnia trancunatula, Viviperous bengalysis, Gyrulus anisus, Limnia auricularia and Limnia accuminata were studied.